Conventional banks Vs Islamic banks : who has better performance? - Sulemane, Shaiza Carimo (2019)
With the goal of getting to know who has a better performance between Conventional and Islamic Banks, five countries with both types of bank, were chosen to be included in this study. Bahrain, Egypt, Jordan, Kuwait and Indonesia, where the first four have passed through the Arab Spring. The analysis is made with data from 98 banks, where 34 are Conventional and 64 are Islamic banks, between 2011 and 2015. Performance was measured in terms of Liquidity, Profitability; Risk and Solvency and Efficiency. The findings of this study indicate that Islamic Banks are more liquid than Conventional Banks, Islamic Banks have a higher Total Equity/Total Assets ratio than Conventional Banks, which is translated into Islamic Banks more sustainable than Conventional Banks and with a low level of risk when lending. Regarding the Bank size, it was found that the higher the bank size, the lower liquidity and solvency will the bank be.